2017
DOI: 10.1093/cvr/cvx135
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidogenic medin induces endothelial dysfunction and vascular inflammation through the receptor for advanced glycation endproducts

Abstract: Medin causes human microvascular endothelial dysfunction through oxidative and nitrative stress and promotes pro-inflammatory signaling in endothelial cells. These effects appear to be mediated via RAGE. The findings represent a potential novel mechanism of vascular injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 42 publications
1
43
0
1
Order By: Relevance
“…4 ), indicative of the formation of medin membrane pores. These results open the possibility to the presence of medin-induced unregulated ionic currents through the plasma membrane, which could alter cellular ionic homeostasis and lead to the endothelial dysfunction and medin-induced EC cytotoxicity observed in vitro ( 33 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…4 ), indicative of the formation of medin membrane pores. These results open the possibility to the presence of medin-induced unregulated ionic currents through the plasma membrane, which could alter cellular ionic homeostasis and lead to the endothelial dysfunction and medin-induced EC cytotoxicity observed in vitro ( 33 ).…”
Section: Discussionmentioning
confidence: 98%
“…Medin is the main constituent of AMA, the most common form of localized amyloid ( 20 ). Little is known about its exact in vivo pathological role; however, ex vivo evidence suggests medin is implicated in multiple cardiovascular disorders ( 28 , 29 , 30 , 31 ), including vascular contributions to neurodegeneration ( 33 , 34 ) and vascular dementia ( 32 ). An in vivo study found higher abundance of nonamyloidogenic medin species in aortas from patients with either thoracic aortic aneurysms or aortic dissection than in control individuals with normal aortas ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ex vivo human adipose and leptomeningeal arterioles, the protein could decrease NO production, increase peroxynitrite, and superoxide production and enhance the expression of the proinflammatory markers such as IL-6 and IL-8 as well as the NF-κB transcription factor. These effects were shown to be mediated through RAGE and inhibition of RAGE by its specific inhibitor, FPS-ZM1, could reverse all such changes [ 50 ].…”
Section: Biology Of the Endothelium And Endothelial Dysfunctionmentioning
confidence: 99%
“…Vascular endothelium is a layer of monocytes on the inner walls of blood vessels, regulating vascular wall function via autocrine and paracrine system. Human vascular endothelial dysfunction is caused by oxidative stress and promoted inflammatory signaling in endothelial cells (Migrino et al 2017). Importantly, vascular inflammation is a main initial effect to induce atherosclerosis that is a complex vascular injury.…”
Section: Introductionmentioning
confidence: 99%